1990
DOI: 10.1557/proc-193-319
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Cluster Impacts on Metallic Targets

Abstract: A modified version of the multiple-interaction code SPUT2 has been used to simulate impacts of 63-atom Cu clusters on six-layer Cu targets.Simulations were carried out with cutoff times of 100 and 500 fs for an incident cluster energy of 63 keV (1 keV/atom).Significant enhancements were observed in the maximum potential and kinetic energies achieved in the early phase of the collision cascade.Some hard collisions yielded atoms with potential energies as high as 92 5 eV (in the CM frame) This is almost twice th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…The non-linear phenomena induced within spikes arise due to multiple collisions between recoiling atoms. 11,14 The energy density per unit volume deposited by a polyatomic ion impact is a function of the total energy, the mass of the projectile and target atoms and the number of constituents in the projectile. Several theories on the repercussions of collision spike formation have been offered, most in the physical context of enhanced sputtering.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The non-linear phenomena induced within spikes arise due to multiple collisions between recoiling atoms. 11,14 The energy density per unit volume deposited by a polyatomic ion impact is a function of the total energy, the mass of the projectile and target atoms and the number of constituents in the projectile. Several theories on the repercussions of collision spike formation have been offered, most in the physical context of enhanced sputtering.…”
Section: Resultsmentioning
confidence: 99%
“…8,9,11 Though not discussed in detail, Benguerba et al 8 observed that the yield of molecular fragments increased more rapidly with the mass and complexity of the polyatomic projectile (for instance, Au n , n = 1-5) than did the yield of deprotonated molecular ions. This observation suggests again a dependence of molecular fragment ion yield on the energy density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation